Negotiating shame: An exploration of the body experience among young South African women who have attended or are attending University - Spyker, Jessica Grace (Rhodes University, Faculty of Humanities, Department of Sociology)
Guided by phenomenological and feminist phenomenological perspectives, this research aimed to explore the ways in which young South African women, who were attending or had recently graduated from university, navigated body shame. It interrogated the socially situated 'lived body' and the way it was impacted by restrictive appearance ideals. Fifteen in-depth interviews were conducted, mostly through the video conferencing website Zoom. It became evident that women experienced their bodies in complex ways. There was evidence of conformity to as well as resistance against the "regime of shame" . Conformity and resistance often happened simultaneously. Both of these kinds of experiences were viewed as valid and explored in their own right. External messages around women's bodies and how they should look had greatly influenced participants experiences of their own bodies. This included messages from discourses such as postfeminism and the body positivity movement, which informed the ways in which they navigated shame.
Keywords: Shame; Body image in women; Body image -- Social aspects; College students -- Social conditions; College students -- Attitudes; Feminist aesthetics; Self-perception in women